2020
DOI: 10.22179/revmacn.22.675
|View full text |Cite
|
Sign up to set email alerts
|

Helminth parasites of bats (Chiroptera, Phyllostomidae) in the Department of Junin, Peru and Check list of records made in Peru

Abstract: Chiroptera are not only important for their great terrestrial diversity, but also for playing ecological roles as prey and predator, arthropod suppression, soil fertility and nutrient distribution, and recycling (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Coleopterans (beetles) are often involved as an intermediate host ( Morgan & Hawkins, 1951 ; Yamaguti, 1961 ; Ubelaker, 1970 ). Low occurrence of parasitism by cestodes in bats was observed in some studies (Nogueira et al ., 2004; Vargas et al ., 2009 ; Angoma et al ., 2020 ). Similarly, cestode also had the lowest infection rate among the three classes of helminths in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Coleopterans (beetles) are often involved as an intermediate host ( Morgan & Hawkins, 1951 ; Yamaguti, 1961 ; Ubelaker, 1970 ). Low occurrence of parasitism by cestodes in bats was observed in some studies (Nogueira et al ., 2004; Vargas et al ., 2009 ; Angoma et al ., 2020 ). Similarly, cestode also had the lowest infection rate among the three classes of helminths in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The overall helminth infection in bats from the Yucatan Peninsula was 26.9%. When we compared this result with other surveys of multiple species of bats, we observed that most studies reported higher infection values, for example in the USA (37.3–63%) (Pistole, 1988 ; Hilton and Best, 2000 ), Mexico (40%) (Salinas-Ramos et al ., 2017 ), Peru (56.7%) (Minaya et al ., 2020 ), Argentina (61.3%) (Milano, 2016 ) and Egypt (43.9%) (Saoud and Ramadan, 1976 ). On the other hand, similar infection levels (20.9–26%) have been reported in bats from Brazil (Nogueira et al ., 2004 ; de Albuquerque et al ., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bats harbor zoonotic viruses such as SARS COVID-19, SARS coronavirus, Nipah virus, Hendra virus, and Ebola virus [7,8]. These small mammals carry protozoans of the genera Plasmodium and Trypanosoma and parasitic helminths, including trematodes, cestodes, and nematodes [9]. Moreover, ectoparasites like ticks, mites, bugs (Hemiptera), fleas (Siphonaptera), and flies (Diptera) parasitize these small mammals [10].…”
Section: Introductionmentioning
confidence: 99%